2002
DOI: 10.1590/s0004-282x2002000500027
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome de Landau-Kleffner e regressão autística: a importância do diagnóstico diferencial

Abstract: RESUMO -Algumas doenças neurológicas podem apresentar sinais e sintomas psiquiátricos, portanto a exploração do diagnóstico etiológico é crucial. O objetivo deste estudo é relatar o caso de um paciente com um distúrbio neurológico, diagnosticado durante internação psiquiátrica. Um menino com desenvolvimento neuropsicomotor normal até 3 anos, quando começou a apresentar crises epilépticas, seguidas por distúrbio de comportamento e deterioração da linguagem. Durante o acompanhamento neurológico, o paciente foi e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
2
0
4
Order By: Relevance
“…27,[37][38][39][40] In addition to formerly discussed studies, some other showing that antiepileptic medications can have a positive impact on behavior, 38,41 and no studies have yet demonstrated that treatment of epileptic disorders positively impact social, language, cognitive, or behavioral outcomes. 6,[26][27][28][29][30][31][32][33][34][35][36][37] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…27,[37][38][39][40] In addition to formerly discussed studies, some other showing that antiepileptic medications can have a positive impact on behavior, 38,41 and no studies have yet demonstrated that treatment of epileptic disorders positively impact social, language, cognitive, or behavioral outcomes. 6,[26][27][28][29][30][31][32][33][34][35][36][37] …”
Section: Resultsmentioning
confidence: 99%
“…29 Many children with primary diagnosis of autism, finally diagnosed as early LKS. The disease identification and final diagnosis is based on clinical judgments, EEG results, symptoms fluctuations and recurrences and there is a little place on a detailed analysis of both the linguistic and behavioral symptoms 30,31 Autism behavior might be a reflective of language loss in these patients or even could be a result of developmental deficit following the epileptic activities which involves both language and "social brain". Finally, a favorable response to an EEG suppression or remission and improvement periods in the language, could be considered as a proof for those whom diagnosis is early form LKS.…”
Section: 18mentioning
confidence: 99%
“…Quando estas são a primeira manifestação, ajudam a estabelecer o diagnóstico, mas até cerca de 1/3 dos pacientes pode mesmo não desenvolver epilepsia. 4,10 Além disso, tal como no caso descrito, as alterações do comportamento podem constituir o primeiro sintoma. Estas podem incluir sintomas de agressividade, alterações do sono, apatia e regressão global social, podendo alternar entre períodos de extrema apatia e outros de comportamento hiperativo/agressivo.…”
Section: Discussionunclassified
“…4 No que respeita às crises epiléticas, raramente são graves e respondem ao tratamento com antiepiléticos convencionais, em regra até à idade adulta. 5,10 Existe ainda uma abordagem cirúrgica, a secção subpial múltipla, cujos resultados são controversos. 6,10 O prognóstico de crianças com SLK é variável.…”
Section: Discussionunclassified
See 1 more Smart Citation